(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper examines the relationship between Resveratrol (RSV), a naturally occurring polyphenol with a reputation for having anti-aggregatory and antioxidant properties, as well as amyloid beta ("Ab1-42"), a central protein in the etiology of “Alzheimer’s disease (AD).” Molecular dynamics (MD) models are used in the study to examine the impact of RSV on the structural behavior and aggregation of “Ab1-42.” The result analysis of the peptide and ligand complex was performed, followed by 200 nanoseconds of interaction at physiological conditions, carried over with root mean square values (RMSD), root mean square fluctuations (RMSF), radius of gyration (Rg), solvent-accessible surface (SASA), secondary structure profiling, and hydrogen bond analysis (HB). The results show that Resveratrol (RSV) is a stable binding partner of “Ab1-42” stabilizing its demand with reduced conformational flexibility, an increase in structural compactness, and reduced solvent exposure. Aggregative protection is hinted at by these changes. Furthermore, the RSV in the form of secondary structure was found to help preserve both β-sheets and α-helix in “Ab1-42.” The experiment confirms the postulation that RSV inhibits the aggregation of “Ab1-42” and provides some evidence to show that RSV may represent a viable therapeutic modulator of “Alzheimer’s disease (AD)” in reducing disease due to its effects.